Analysis of the Tourism Potential of Tanjung Lapin Beach, North Rupat District, Bengkalis Regency - Riau Nurita; Firdaus Yusrizal; Ahmad Nawawi; Fahmi Muhammad; Nurarini Yulia (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
Tanjung Lapin Beach is a tourist destination with natural potential in North Rupat District. This study was conducted to analyze the tourism potential of Tanjung Lapin Beach in North Rupat. This research method used descriptive analysis and SWOT. The results of this study indicate that Tanjung Lapin Beach has natural beauty with white sand, cultural attractions, security and cleanliness of the location, friendly residents, and has more complete tourism facilities than other tourist attractions on Rupat Island. To analyze the right strategy in developing Tanjung Lapin Beach to obtain development results, it is recommended to use an aggressive strategy. It is necessary to develop tourism potential, conduct promotions, empower local communities in the field of entrepreneurship, empower and improve services for business actors in the field of tourist accommodation, and develop businesses as income to increase PAD and local community.